Asset Pricing When Traders Sell Extreme Winners and Losers - An, Li (Review of Financial Studies, 2016)
This study investigates the asset pricing implications of a newly documented refinement of the disposition effect, characterized by investors being more likely to sell a security when the magnitude of their gains or losses on it increases. I find that stocks with both large unrealized gains and large unrealized losses outperform others in the following month (trading strategy monthly alpha = 0.5-1%, Sharpe ratio = 1.5). This supports the conjecture that these stocks experience higher selling pressure, leading to lower current prices and higher future returns. Overall, this study provides new evidence that investors' trading behavior can aggregate to affect equilibrium price dynamics.